2004
DOI: 10.1042/bj20030977
|View full text |Cite
|
Sign up to set email alerts
|

Cobatoxin 1 from Centruroides noxius scorpion venom: chemical synthesis, three-dimensional structure in solution, pharmacology and docking on K+ channels

Abstract: CoTX1 (cobatoxin 1) is a 32-residue toxin with three disulphide bridges that has been isolated from the venom of the Mexican scorpion Centruroides noxius Hoffmann. Here we report the chemical synthesis, disulphide bridge organization, 3-D (three-dimensional) solution structure determination, pharmacology on K+ channel subtypes (voltage-gated and Ca2+-activated) and docking-simulation experiments. An enzyme-based cleavage of the synthetic folded/oxidized CoTX1 indicated half-cystine pairs between Cys3-Cys22, Cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
36
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 44 publications
2
36
0
1
Order By: Relevance
“…However, recent studies by Rizzi et al (29), using expressed Na v 1.1-1.6 ␣-subunits, did not find an interaction between crotamine and Na v channels. Further support for the interaction of defensin-like toxins with K v ion channels derives from recent structural mapping of the K v channel surface and, in some cases, toxin/channel complexes (23)(24)(25). Together, these facts support the concept that hBD-2 and crotamine may preferentially but not exclusively target respective Na v, NaK v , or other TTX-sensitive ion channelsversus K v channels-contributing to their net cytotoxic effects.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…However, recent studies by Rizzi et al (29), using expressed Na v 1.1-1.6 ␣-subunits, did not find an interaction between crotamine and Na v channels. Further support for the interaction of defensin-like toxins with K v ion channels derives from recent structural mapping of the K v channel surface and, in some cases, toxin/channel complexes (23)(24)(25). Together, these facts support the concept that hBD-2 and crotamine may preferentially but not exclusively target respective Na v, NaK v , or other TTX-sensitive ion channelsversus K v channels-contributing to their net cytotoxic effects.…”
Section: Discussionsupporting
confidence: 49%
“…In turn, this cationic facet binds to 4 highly conserved Asp 452 residues symmetrically distributed on the extracellular P-loops of K v tetramers (27). In addition, a highly-conserved aromatic residue, typically Phe or Tyr, also participates in this pore-occluding complex, forming the classical cationic-aromatic residue dyad (25). Collectively, the current data support the hypothesis that residue-specific differences in peptides that have conserved overall 3D homology may contribute to target ion-channel preferences.…”
Section: Discussionmentioning
confidence: 99%
“…This protrusion is deep enough such that there is electrostatic repulsion between the lysine side chain and K + ions occupying the pore [35,40]. The critical lysine residue was found to interact with the tyrosine residue of the GYG sequence during kaliotoxin block of the mKv1.3 channel, but for other toxin-channel pairs its interaction with other pore residues was described [35,[41][42][43]. Since the selectivity filter is formed by backbone carbonyl oxygens, the protruding toxin residues do not interact with the side-chain atoms of the selectivity filter residues [36].…”
Section: Pore Architecture Sites Important For Toxin Bindingmentioning
confidence: 95%
“…Docking and electrophysiological experiments with Pi1 analogs have demonstrated that a ring of basic residues (Arg5, Arg12, Arg28 and Lys31) interacts with acidic residues of the K V channel turrets located in the most extracellular part of the channel outer vestibule. Moreover, three-dimensional models of toxin-channel interactions generated with scorpion toxins Pi4 (from Pandinus imperator), cobatoxin 1 (Centruroides noxius), iberiotoxin (Mesobuthus tamulus), maurotoxin (Scorpio maurus palmatus) and Lq2, agitoxin2 and charybdotoxin from Leiurus quinquestriatus hebraeus have all suggested that other amino acid residues surrounding the functional dyad make important contacts with specific residues at the turret regions of the KcsA (from Streptomyces lividans), K V 1.x and calcium-activated potassium (K Ca 1.1 and K Ca 3.1) channels [33][34][35][36][37][38]. Therefore these findings support our hypothesis that BcsTx3 binds to Shaker IR channels through a multipoint interaction, and thus other amino acids than those of the selective filter might be involved in its binding and contribute to the observed potentiated blockage.…”
Section: Discussionmentioning
confidence: 99%